2011
DOI: 10.2215/cjn.07700910
|View full text |Cite
|
Sign up to set email alerts
|

Brachial-Ankle Pulse Wave Velocity and Rate of Renal Function Decline and Mortality in Chronic Kidney Disease

Abstract: SummaryBackground and objectives Increased arterial stiffness was reported to be associated with decreased estimated GFR (eGFR). Previous studies suggested that arterial stiffness might play a role in renal function progression in patients with chronic kidney disease (CKD). The aim of this study was to investigate whether there was an independent association between brachial-ankle pulse wave velocity (baPWV), a marker of arterial stiffness, and renal function progression in CKD patients.Design, setting, partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
106
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 106 publications
(116 citation statements)
references
References 33 publications
9
106
1
Order By: Relevance
“…Thus, baPWV has gradually come into clinical use. Many studies have reported the association between baPWV and CVD [11][12][13][14][15] ; therefore, our results of the cut-off value of baPWV for predicting cardiovascular prognosis could extend the usefulness of baPWV to the management of hypertensive patients in clinical settings.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Thus, baPWV has gradually come into clinical use. Many studies have reported the association between baPWV and CVD [11][12][13][14][15] ; therefore, our results of the cut-off value of baPWV for predicting cardiovascular prognosis could extend the usefulness of baPWV to the management of hypertensive patients in clinical settings.…”
Section: Discussionmentioning
confidence: 74%
“…We can calculate baPWV easily and automatically using pressure cuffs on the brachial and tibial arteries. Many studies have investigated the clinical significance of baPWV 9,10) , which has been revealed to correlate significantly with coronary artery disease 11) , declined renal function 12) , and total mortality 13) . We previously reported the clinical usefulness and limitations of baPWV 14,15) , which has a close correlation with cfPWV 16) .…”
Section: Introductionmentioning
confidence: 99%
“…Blood pressure might also influence renal outcomes in CKD patients. 7 We statistically adjusted for mean arterial pressure in the multivariate analysis and still found that high baPWV and bPEP/bET was significantly associated with rapid renal progression and renal endpoints.…”
Section: Discussionmentioning
confidence: 91%
“…5,6 We recently evaluated the influence of baPWV, a marker of arterial stiffness, on renal function progression in a cohort of patients with moderate to advanced CKD and found that baPWV was independently associated with renal function decline and progression to commencing dialysis or death. 7 One possible mechanism is that increased arterial stiffness might result in greater transmission of elevated systemic blood pressure to the glomerular capillaries, thereby exacerbating glomerular hypertension, a major determinant of progressive renal damage. 19,20 Similarly, when comparing the two groups with high baPWV, only the group that also had high bPEP/bET was associated with adverse renal outcomes (vs. low baPWV and bPEP/bET).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation